Effect of heat-treatment atmosphere on the current generation of TiO2 nanotube array electrodes in microbial fuel cells. (10th December 2017) - Huang, Lijie; Zhang, Xueqing; Shen, Dongsheng; Li, Na; Ge, Zhipeng; Zhou, Yuyang; Zhou, Mengjiao; Feng, Huajun; Guo, Kun
Highlights: High current density achieved on modified Ti electrode heated in a H2 atmosphere. Electrode specific surface area increased greatly after electrochemical oxidation. Highest electrode/biofilm electron transfer rate achieved for H2 treated electrode. Abstract: We investigated the effects of the heat-treatment atmosphere on the current generation of Ti electrodes in microbial fuel cells (MFCs). The maximum current density was achieved for TiO2 nanotube array electrodes heated in H2 (TNA-H2 ) (22.69 ± 0.18 A m −2 ). Physical analysis of the Ti electrode surfaces revealed that the specific surface area increased after electrochemical anodization. The crystallinities of the TiO2 nanotube array electrodes heated in H2 (81.66%), CH4 (74.48%), N2 (59.67%), and O2 (44.82%) showed a significant positive correlation with the corresponding current densities (P < 0.05, R 2 = 0.9469). In addition, the highest electron transfer rate constant was achieved for TNA-H2 (2.38 s −1 ). The large specific surface area, good chemical stability, high electron transfer rate, and good biocompatibility of TNA-H2 suggest its great potential for application as an anode system in MFCs.